Penguatan Kerjasama ASEAN Maritime Forum (AMF) dalam Penanganan Kejahatan Lintas Negara - Alif Oktavian (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
The ASEAN region is a region that has abundant natural resources, almost all countries in the ASEAN region are bordered by oceans, so they are vulnerable to problems in the region. The large number of crimes that occur in maritime border areas between ASEAN countries have encouraged the formation of organizations that intend to highlight crime problems that occur across countries, including crimes of corruption, drug trafficking in people and others. The ASEAN Maritime Forum is a dialogue forum related to Maritime/Maritime issues, one of the aims of which is that maritime security is one of the goals that ASEAN countries wish to realize in maintaining security stability around borders, especially those bordered by the sea. This investigation adopts a qualitative research approach, a scientific method commonly utilized by researchers in the social sciences. Qualitative research involves a team of researchers who employ systematic methods to explore social phenomena and human issues. The selection of this approach is rooted in the rationale that it enables the preservation of the object's integrity, treating various research-related data as an interconnected whole.